Violent Fathers and Runaway Sons: Colonial Relationships in Une vie de boy and Mission terminée - Laurie Corbin (Studies in 20th & 21st Century Literature, 2003)
This study examines familial relationships in two novels published by Ferdinand Oyono and Mongo Beti shortly before Cameroon's independence in 1960, making use of three levels of analysis. The first shows the impact of colonization on familial and social structures, in particular the ways in which the weakening of the traditional hierarchy leads to the flight of young men from their families and villages. The second looks at the two novels as showing the relationship of France (who was often represented as a kindly parent to its colonies), the colonized countries, and their citizens: the unpredictable and brutal father can be seen as representing the French, the helpless and brutalized mother the colonized country, and the protagonist the colonized person "orphaned" by colonialism. The third level of analysis makes use of Lacanian theory, in particular Lacan's theorization of the accession to the Symbolic order, to examine the place of language and what could be described as the Law of the Father in these texts. These different levels of analysis show the ways in which these writers were addressing the problems of colonies moving toward independence after having been crippled—socially, economically, politically, and psychologically—by years of foreign domination.
Keywords: family; familial relationship; Ferdinand Oyono; Mongo Beti; Cameroon; colonization; social structure; mother; father; young men; orphan; foreign domination; abuse